Influence of alternative drying aids on water sorption of spray dried mango mix powders: a thermodynamic approach - Cano-Higuita, Diana Maria [UNESP]; Villa-Vélez, Harvey Alexander [UNESP]; Telis-Romero, Javier [UNESP]; Váquiro, Henry Alexander; Nicoletti Telis, Vânia Regina [UNESP] (Inst Chemical Engineers, 2015)
Mango pulp mixed with drying aids (maltodextrin and skimmed milk) was spray dried to obtain three powder formulations. The water sorption behavior of these mango mix formulations was determined at temperatures of 20, 30, 40 and 50 degrees C in water activity ranging between 0.059 and 0.907. The Guggenheim, Anderson and De Boer (GAB) model was applied to modeling the adsorption isotherms of mango mix powders, resulting in statistical values of mean relative error (MRE <= 5.14%). Differential and integral thermodynamic properties related to water sorption for the mango powders were determined by the analytical derivation of the water activity with respect to temperature based on the GAB model fitting. The differential thermodynamic properties indicated a decrease in the water sorption energy with increasing water content and the negative values of the Gibbs free energy revealed that the sorption process was spontaneous for the three powder formulations. In spite of the formulation containing skimmed milk have shown the higher monolayer water contents, the minimal integral entropy zone observed at similar values of water activity for the three mango mix powders indicated that all of them could be safely stored at the same relative humidity condition. (C) 2013 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Spray drying; Modeling; Thermodynamic properties; Carrier agents; Sorption isotherms